Advancing nursing practice for improved health outcomes using the principles of perceptual control theory. (27th May 2020) - Griffiths, Robert; Carey, Timothy A.
Abstract: This article describes how an empirically supported theory of human behaviour, perceptual control theory, can be used to advance nursing practice and improve health outcomes for people who are accessing nursing care. Nursing often takes a pragmatic approach to the delivery of care, with an emphasis on doing what appears to work. This focus on pragmatism can sometimes take precedence over any consideration of the underlying theoretical assumptions that inform decisions to take one particular approach over another or the mechanisms through which nursing interventions have their effects. For nursing to develop as a profession, there needs to be an increased focus on the core principles that underpin the delivery of care. In addition to understanding what works, nurses must develop their understanding of how and why particular approaches work or do not work. Understanding the fundamental principles that underpin nurses' actions will lead to more efficient and effective approaches to the delivery of nursing care. It will also enable nurses to maximize those elements of their practice that are most beneficial for people and minimize other activities that either have little effect or actually lead to worse outcomes. In this article, we will propose that the phenomenon of control is fundamental to human health. Perceptual control theory provides a coherent theoretical framework that enables us to understand the phenomenon of control through a functional model of human behaviour. People are healthy when their neurochemical, physiological, biological, psychological and social states are all controlled satisfactorily. We will explain the implications of understanding health as control throughout the paper. From this perspective, we will argue that the aim of nurses and nursing should be to support people to maintain or recover control over those aspects of their lives that are important and meaningful to them.